Parametric optimization and analysis of thermodynamic venting system in liquid hydrogen tank under microgravity. (18th November 2021) - Zheng, Yongyu; Yang, Peng; Liu, Yingwen; Yang, Qi; Yan, Chunjie; Wang, Xiaojun
Abstract: This paper used the lumped vapor model to simulate the self-pressurization and thermodynamic venting process in the cryogenic liquid hydrogen tank with 90% filling rate under microgravity. Based on the orthogonal experiment, twenty-five cases with different parameters were designed. Daily evaporation rate and cooling capacity utilization efficiency were proposed to evaluate the exhaust loss during the jet process and depressurization efficiency during depressurization process. The four parameters of spray bar including exhaust rate, diameter of inner tube of heat exchanger, nozzle length and number of nozzles were optimized and the weight of influence on the daily evaporation rate and cooling capacity utilization efficiency was analyzed. Results showed that nozzle length and number of nozzles played a key role in the daily evaporation rate and cooling capacity utilization efficiency, while diameter of inner tube of heat exchanger had little effect. Under the same mass flow, smaller nozzle length, lower exhaust rate and fewer nozzles could increase the inlet velocity, thereby reducing the daily evaporation rate and improving the cooling capacity utilization efficiency. The thermal stratification could be eliminated well. In addition, arranging two nozzles up and down was more advantageous than arranging a single nozzle in the middle. The research results were useful for improving the efficiency of the thermodynamic venting system (TVS) and extending the propellant storage time in orbit. Highlights: The lumped vapor model of TVS was established. The influences of TVS parameters on the depressurization were studied. The weight of influence of TVS parameters was evaluated. The optimal parameters of TVS were obtained.